2005
DOI: 10.1037/0022-0167.52.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attachment, Affect Regulation, Negative Mood, and Interpersonal Problems: The Mediating Roles of Emotional Reactivity and Emotional Cutoff.

Abstract: This study examined the mediating role of affect regulation among attachment, negative mood, and interpersonal problems. Participants were 229 college students at a large midwest university. Structural equation modeling indicated attachment anxiety and avoidance contributed to negative mood and interpersonal problems through different and distinct affect regulation strategies (i.e., emotional reactivity or emotional cutoff). The association between attachment anxiety, negative mood, and interpersonal problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
274
2
19

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 329 publications
(322 citation statements)
references
References 50 publications
(97 reference statements)
27
274
2
19
Order By: Relevance
“…Brennan et al (1998) also reported that the ECRS was positively correlated with similar theoretical constructs, such as touch and postcoital emotions. Likewise, Wei et al (2005) found positive correlations between attachment anxiety and emotional reactivity and between attachment avoidance and emotional cutoff. reported test-retest reliabilities of .68 and .71 over a 6-month interval for the attachment anxiety and attachment avoidance scales, respectively.…”
Section: Measures Attachment (Time 1)mentioning
confidence: 96%
See 3 more Smart Citations
“…Brennan et al (1998) also reported that the ECRS was positively correlated with similar theoretical constructs, such as touch and postcoital emotions. Likewise, Wei et al (2005) found positive correlations between attachment anxiety and emotional reactivity and between attachment avoidance and emotional cutoff. reported test-retest reliabilities of .68 and .71 over a 6-month interval for the attachment anxiety and attachment avoidance scales, respectively.…”
Section: Measures Attachment (Time 1)mentioning
confidence: 96%
“…A review of the empirical studies on attachment and coping strategies reveals that some research has supported the theory that individuals with high levels of attachment anxiety and/or avoidance use distinct strategies. For example, Wei et al (2005) found that attachment anxiety contributed to negative mood (i.e., depression and anxiety) through emotional reactivity (but not emotional cutoff); by contrast, attachment avoidance contributed to negative mood through emotional cutoff (but not emotional reactivity). Other studies have not shown that individuals with high levels of attachment anxiety use distinct coping strategies in contrast with individuals with high levels of attachment avoidance.…”
Section: Attachment Ineffective Coping and Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…La evidencia de validez de constructo de la ERC está basada en estudios que muestran que es un predictor significativo de constructos teóricamente relevantes, tales como la satisfacción marital (Brennan et al, 1998) y la presencia de problemas interpersonales (Wei, Vogel, Ku & Zakalik, 2005). De acuerdo con el análisis de validez del instrumento en Chile, Spencer, Guzmán, Fresno y Ramos (2013) afirman que el análisis de validez de constructo indica que en términos generales los puntajes de las escalas de la versión chilena de la ERC se relacionan de la manera esperada con el cuestionario de apego adulto CaMir (Garrido, Santelices, Pierrehumbert & Armijo, 2009).…”
Section: Escala De Experiencia En Relaciones Cercanas (Erc)unclassified